Li+-clipping for edge S-vacancy MoS2 quantum dots as an efficient bifunctional electrocatalyst enabling discharge growth of amorphous Li2O2 film. (November 2019) - Sun, Zemin; He, Jinlu; Yuan, Mengwei; Lin, Liu; Zhang, Zheng; Kang, Zhuo; Liao, Qingliang; Li, Huifeng; Sun, Genban; Yang, Xiaojing; Long, Run; Zhang, Yue
Abstract: Molybdenum disulfide (MoS2 ), as an extremely intriguing two-dimensional (2D) material with excellent electrocatalyst, has attracted more and more attentions in recent years. However, the lack of precisely engineered rich-edge S-vacancy MoS2 constitutes a major obstacle for in-depth studying of structure-activity relationship of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Herein, based on Lewis acid-base theory, we prepared rich-edge S-vacancy MoS2 quantum dots (MoS2 QDs) via top-down strategy using lithium bis(trifluoromethylsulphonyl)imide as a stripper and clipper. It is demonstrated for the first time that the rich-edge S-vacancy MoS2 QDs exhibit an extraordinary ORR/OER catalytic performance in Li-O2 batteries system by a joint experimental and theoretical study. Importantly, the rich-edge S-vacancy MoS2 QDs can run more than 230 cycles at high current density, which was almost 9 times longer than the cycle stability of bulk MoS2 . The excellent activity arises primarily due to that the MoS2 QDs facilitate conformal growth of amorphous Li2 O2 film on the cathode, originating from the significant differences of adsorption energies between Li + and O2, which could significantly enhanced Li2 O2 formation/decomposition kinetics. This work provides a novel way for controllable synthesis of rich-edge S-vacancy MoS2 QDs, establishes the underlying mechanisms for the high OER/ORR activity, and suggests high translatability to apply other TMDs. Graphical abstract: Through clipping bulk MoS2 to obtain rich edge S-vacancy MoS2 QDs showed outstanding ORR and OER electrocatalytic properties in Li-O2 battery, which gives a new way to improve ability for LOBs by QDs.Image 1 Highlights: Achieving an atomic level prepare the edge S-vacancy on MoS2 quantum dots based on Lewis acid-base theory. Rich-edge S-vacancy MoS2 QDs facilitate conformal growth of amorphous Li2 O2 film on the cathode. Our study for the first time proves that rich-edge S-vacancy MoS2 QDs is an extraordinary bifunctional catalyst.